Polysulfone/polyurethane blend degradable hollow fiber membranes preparation and transport–separation properties evaluation. Issue 47 (7th October 2016) - Wojciechowski, Cezary; Chwojnowski, Andrzej; Granicka, Ludomira; Łukowska, Ewa; Grzeczkowicz, Marcin
Abstract: The method of preparation of partly degradable polysulfone/polyurethane (PSf/PU) asymmetric hollow fiber membranes is presented. The membranes built of PSf and polyurethane polymer containing degradable ester groups were obtained by dry/wet-spinning phase-inversion technique then treated with sodium hydroxide solution using the flowing method. The membrane hydraulic permeability (UFC) for pure water and retention coefficients were evaluated for chosen markers before and after applied hydrolysis. An increase in ultrafiltration coefficient was observed while retention coefficient did not change significantly in post-treatment membranes. Hydrolysis caused the partial removal of PU from the membrane structure resulting in the opening of the pore passages and the permeability increase without increasing the pore size. The morphology of the PSf/PU hollow fiber membranes was analyzed using scanning electron microscopy before and after hydrolysis.